Cloning and function of the cyclin‐dependent kinase 9 gene in ovarian development of the ridgetail white prawn, Exopalaemon carinicauda. (29th August 2022) - Zhang, Pan; Li, Yongchuang; Zheng, Duwei; Hua, Songsong; Song, Chongyang; Li, Zhengmin; Shi, Tingting; Wang, Panpan; Yan, Binlun; Li, Jitao; Gao, Huan
Abstract: To investigate the key genes affecting ovarian development in the ridgetail white prawn, Exopalaemon carinicauda, we cloned the full‐length cDNA of the CDK 9 gene and discussed its role in ovarian development. Our results show that the gene has an open reading frame of 1155 bp, encoded 383 amino acids, and it has a conserved cyclin binding motif S_TKc. The open reading frame of CDK 9 was expressed as a 43.96 Kda molecular weight protein. The phylogenetic tree analysis showed that the CDK 9 gene has the highest homology with the CDK 9 genes of Penaeus vannamei and Penaeus japonicus . The results of qRT‐PCR show that the CDK 9 gene was also expressed in the eye stalk, stomach, heart, gill, intestine, muscle, ovary, hepatopancreas and ventral cord. The expression level was highest in the ovary, which was significantly different from the other tissues ( p < 0.05). In the five stages of ovarian development, the expression level of the CDK 9 gene was highest in stage I, which was significantly different from the other stages ( p < 0.05). In situ hybridization tests showed strong expression signals in the membrane, cytoplasm and nucleus of oocytes and previtellogenic oocytes. Nevertheless, following the proliferation of oocytes, the expression signals became much stronger in the oocyte membrane and in the whole follicular cells located in the interstitial space. The RNA interference results show that the expression of the CDK 9 gene significantly affects the expression of the Vg and VgR genes. Our findings suggest that CDK 9 plays an important role in the synthesis and transportation of vitellin.